Keefektifan Model Pembelajaran Contextual Teaching and Learning Berbasis Teknologi Informasi untuk Meningkatkan Rasa Percaya Diri dan Hasil Belajar Siswa - Maulana, Andi; Sutono, Agus; Sumarno, Sumarno (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The background that drives this research is the low level of self-confidence in the cognitive learning outcomes of fifth grade elementary school students in Tlogohendro village. This type of research is quantitative research in the form of pre-experimental with the type of one group pre-test and post-test design. The population of this study were fifth grade elementary school students in Tlogohendro village for a total of 35 in the 2022/2023 academic year with a saturated sample. The data in this study were obtained through tests and documentation.The posttest results showed that the percentage of classical group learning completeness at both SDN 01 Tlogohendro, SDN 02 Tlogohendro and SDN 03 Tlogohendro reached 100%. And based on the analysis of student learning outcomes, t'count (36.74) ttable (1.7), thus Ha is accepted, which means that there is a significant difference in scores between before and after students apply contextual teaching and learning based on information technology.So it is concluded that the contextual teaching and learning model based on information technology is effective in increasing the self-confidence and cognitive learning outcomes of class V state elementary school students in Tlogohendro village.